Simulation of non-volatile memory cell using chalcogenide glasses - Rocca, Javier Alejandro (2012)
In this paper, a non-volatile memory cell of Te-based chalcogenide material is proposed and modeled. It is formed by layers of three materials: an insulating material, a conductor and a sensitive material: Te-based chalcogenide material. A 2D model using a finite element method has been developed for the simulation of the thermal behaviour of the cell. Temporal evolution of temperature maps is obtained. The model is applied to alloys of the Ge-Sb-Te system. The computed results allow us to understand the role played by the variables involved (thickness of different layers, cell radius, composition of the chalcogenide glass) in order to optimize the cell structure.